Controlled-release nanoencapsulating microcapsules to combat inflammatory diseases - Baek JS; Yeo EW; Lee YH; Tan NS; Loo SCJ (Dove Medical Press, 2017)
Jong-Suep Baek,1 Eng Wan Yeo,1 Yin Hao Lee,2 Nguan Soon Tan,2 Say Chye Joachim Loo1,3 1School of Materials Science and Engineering, Nanyang Technological University, Singapore; 2School of Biological Sciences, Nanyang Technological University, Singapore; 3Singapore Centre on Environmental Life Sciences Engineering (SCELSE), Nanyang Technological University, Singapore Abstract: The World Health Organization (WHO) has reported that globally 235 million people suffer from chronic and other inflammatory diseases. The short half-lives of nonsteroidal anti-inflammatory drugs (NSAIDs) and their notoriety in causing gastrointestinal discomforts, warrants these drugs to be released in a controlled and sustained manner. Although polymeric particles have been widely used for drug delivery, there are few reports that showcase their ability in encapsulating and sustaining the release of NSAIDs. In this paper, polymeric nanoencapsulating microcapsules loaded with NSAIDs were fabricated using solid/water/oil/water emulsion solvent evaporation method. Two NSAIDs, ibuprofen and naproxen, were first pre-loaded into nanoparticles and then encapsulated into a larger hollow microcapsule that contained the third NSAID, celecoxib. A high encapsulation efficiency (%) of these NSAIDs was achieved and a sustained release (up to 30 days) of these drugs in phosphate-buffered saline was observed. Then, a gastrointestinal drug – cimetidine (CIM) – was co-loaded with the NSAIDs. This floating delivery system exhibited excellent buoyancy (~88% up to 24 h) in simulated gastric fluid. It also allowed a sequential release of the drugs, whereby an immediate release of CIM followed by NSAIDs was observed. Drug release of the NSAIDs observed Fickian diffusion mechanism, whereas CIM observed non-Fickian diffusion. Therefore, this delivery system is a promising platform to control the delivery of NSAIDs to combat inflammatory diseases, thereby protecting against possible gastrointestinal side effects that may arise from the overuse of NSAIDs. Keywords: NSAIDs, multi-drug encapsulation, sequential release, floating oral drug delivery, injectable system, oral delivery systems, diffusion, emulsion, sustained release